Male and Female Witnesses’ Speech in Swedish Criminal Trials - Waara, Elin; Shaw, Philip (HERMES - Journal of Language and Communication in Business, 2006)
The present quantitative study focuses on witnesses’ speech in Swedish criminal trials, more speciﬁcally on potential differences between men’s and women’s language styles. Since the 1970s, research on language and gender has been divided into three main approaches towards the relationship between men’s and women’s language use: the deﬁcit approach, the dominance approach and the cultural approach. The present study uses the more recent dynamic approach to show how gender is acted out in each situation taking into account a number of factors, e.g. context. The aim of our work is ﬁrst and foremost to study the possible correlation between the witnesses’ gender and language in the courtroom context and then to investigate if income and/or level of education provide better explanations for possible variation by looking at a broad range of linguistic variables. The results show no statistically signiﬁcant gender or social status differences in the witnesses’ speech. However, when comparing the results of the testifying police ofﬁcers accidentally included in the study with the rest of the witnesses, the differences turned out to be signiﬁcant. This shows that, in this case, factors such as previous courtroom experience and familiarity with the context were probably more inﬂuential on the speech of the informants than gender, income and education, in conformity with the assumptions of the dynamic approach.